Trends of participation and utilitarianism of nature in Chiapas-Mexico. A comparative analysis - Céspedes Ochoa, Elizabeth (2017)
Development policies have tended to be used as hegemonic instruments to legitimize forms of dependence and to justify the depredation of natural resources, in such a way that it gives distinctive features to Mexico's development policies at the federal and state levels. This article presents the perspective of the strategic construction of development policies in Mexico, from an analysis of comparative trends with the strategies of the Chiapas development plans, addressed in terms of state participation, focus on the use and management of Natural resources and relationships with indigenous populations.